Mineral intake independent from gastric irritation or pica by cell-dehydrated rats - Constancio, Juliana [UNESP]; Pereira-Derderian, Daniela T. B. [UNESP]; Menani, José Vanderlei [UNESP]; De Luca, Laurival A. [UNESP] (Pergamon-Elsevier B.V. Ltd, 2011)
Gavage of 2 M NaCl (IG 2 M NaCl), a procedure to induce cell-dehydration-and water and 015 M NaCl intake in a two-bottle choice test-is also a potential gastric irritant. In this study, we assessed whether mineral intake induced by IG 2 M NaCl is associated with gastric irritation or production of pica in the rat. We first determined the amount of mineral solution (0.15 M NaCl, 0.15 M NaHCO3, 0.01 M KCl and 0.05 mM CaCl2) and water ingested in response to IG 2 M NaCl in a five-bottle test. Then, we used mineral solutions (0.01 M KCl and 0.15 M NaHCO3), whose intakes were significantly increased compared to controls, and water in three-bottle tests to test the gastric irritation hypothesis. The IG 2 M NaCl induced KCl and NaHCO3 intake that was not inhibited by gavage with gastric protectors Al(OH)(3) or NaHCO3. IG 2 M NaCl or gavage of 0.6 N acetic acid induced mild irritation, hyperemia, of the glandular part of the stomach. A gavage of 50% ethanol induced strong irritation seen as pinpoint ulcerations. Neither ethanol nor acetic acid induced any fluid intake. Neither IG 2 M NaCl nor acetic acid induced kaolin intake, a marker of pica in laboratory rats. Ethanol did induce kaolin intake. These results suggest that IG 2 M NaCl induced a mineral fluid intake not selective for sodium and independent from gastric irritation or pica. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Dehydration; Thirst; Sodium appetite; Mineral lick; Self-medication; Gastric mucosa